1996
DOI: 10.1093/tropej/42.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Iron status of newborns born to iron deficient anaemic mothers

Abstract: Haemoglobin, serum iron, total iron binding capacity, and serum ferritin were determined in newborns of 16 mothers with iron deficiency anaemia, 28 mothers with non-anaemic iron deficiency, and nine mothers with normal haemoglobin and serum ferritin levels. The results showed that there were no significant differences in the mean values of haemoglobin, serum iron, and total iron binding capacity among the newborns in the three groups. However, the mean value of serum ferritin differed significantly among the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
2
19
0
3
Order By: Relevance
“…The compensatory increase in FRmediated iron transport would be able to keep a constant iron supply from mother to fetus, although pregnant women with mild iron de®ciency and moderate iron de®ciency anemia have`inadequate' iron. It is probably the reason why iron status in fetuses whose mother is suffering from iron de®ciency is normal or nearly normal, as reported by some research groups (Gebre-Medhin & Birgegard, 1981;Dallman, 1989;Bhargava et al, 1991;Lao et al, 1991;Institute of Medicine, Food and Nutrition Board, 1993;Hokama et al, 1996). Our results also show that there is no signi®cant difference in FnRs between pregnant women with severe iron de®ciency anemia and with normal measurements.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The compensatory increase in FRmediated iron transport would be able to keep a constant iron supply from mother to fetus, although pregnant women with mild iron de®ciency and moderate iron de®ciency anemia have`inadequate' iron. It is probably the reason why iron status in fetuses whose mother is suffering from iron de®ciency is normal or nearly normal, as reported by some research groups (Gebre-Medhin & Birgegard, 1981;Dallman, 1989;Bhargava et al, 1991;Lao et al, 1991;Institute of Medicine, Food and Nutrition Board, 1993;Hokama et al, 1996). Our results also show that there is no signi®cant difference in FnRs between pregnant women with severe iron de®ciency anemia and with normal measurements.…”
Section: Discussionsupporting
confidence: 84%
“…However, the function of this compensatory system is believed to be limited based on the fact that the Tf saturation is remarkably decreased and the TfR expression is also hindered in pregnant women with severe iron de®ciency (Singla et al, 1996;Allen, 2000). In addition, it was reported that iron status in fetuses whose mothers were suffering from iron de®ciency is normal or nearly normal, being independent of maternal iron status (Gebre-Medhin & Birgegard, 1981;Dallman, 1989;Bhargava et al, 1991;Lao et al, 1991;Institute of Medicine, food and Nutrition Board, 1993;Hokama et al, 1996), although different results have been reported (Blot et al, 1999). These ®ndings imply that there might be some other mechanisms involved in the regulation of maternal-fetal iron transport.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Japanese study showed that a group of 16 mothers with iron de®ciency anaemia gave birth to infants with lower serum ferritin levels than those of non-iron de®cient mothers (Hokama et al, 1996), however, although a signi®cant proportion of the women were taking supplementary iron the study did not assess the diets of the women.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there might be developmental effects on the infant, for example, a recent study with a very small number of subjects has shown that the infants of mothers with iron de®ciency anaemia are born with lower serum ferritin levels than those of iron-replete mothers, this may increase the risk of them developing anaemia subsequently (Hokama et al, 1996). The ALSPAC study is well placed to investigate this fully in a large cohort.…”
Section: Discussionmentioning
confidence: 99%